(untitled) - Langmi, Henrietta Wakuna

Synthesis and characterization of zeolitic imidazolate framework derived activated carbon materials for carbon dioxide adsorption (University of Pretoria, 2025)
Dissertation (MSc (Chemistry))--University of Pretoria, 2024.